PREPARATION AND CHARACTERIZATION OF TiO2-ZrO2 COATING PREPARED BY SOL-GEL SPIN METHOD (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Spin coating is used in various industrial and engineering applications, inducing the producing of thin films within nano-scale boundaries. In industrial processes, different substrates can be subjected to spin coatings, for example, micro microfilms, etc. In this research, Titanium tetra-isoperopoxide (TTIP) is used in the preparing of composite coatings by sol-gel spin method. The structure and chemical compositions of the composite coatings are studied using X-ray, SEM and EDS methods. The XRD pattern clearly shows the additions of 2% and 4% ZrO2 and their effects on the morphology and crystalline structure of titanium oxide, in addition; increasing the additives of ZrO2 in TiO2 films improves the intensity of diffraction peaks. The optical photographs show the microstructure of TiO2 doped 2% and 4% ZrO2 crystallization beads film measured to be 100.81 ?m and TiO2 doped with (2 and 4% ZrO2) films are approximately 122.8813 ?m in thickness. The SEM results of pure sol-gel TiO2 are relatively smooth, almost uniform dispersion of ZrO2 particles occurs in the matrix. The EDX results show the presence of the Ti and high amounts of Zr in the structure of the matrix. Coating hardness measurements exceed 70% with doped TiO2 and it increases with increasing the amount of zirconia.